Universal neonatal hearing screening program in Shanghai, China: An inter-regional and international comparison. (November 2016) - Fang, Xingang; Li, Xi; Zhang, Qi; Wan, Jin; Sun, Mei; Chang, Fengshui; Lü, Jun; Chen, Gang
Abstract: Objective: By comparing the Universal Neonatal Hearing Screening (UNHS) program as implemented in Shanghai and other regions in China and countries around the world, this study makes an assessment of the Shanghai model and summarizes the experiences implementing the UNHS program, so as to provide a valuable reference for other countries or regions to carry out UNHS more effectively. Since Shanghai is one of the most developed regions in China, we also examined the relationship between economic development and the UNHS starting year and coverage rate. Methods: The study conducted a systematic review of published studies in Chinese and English on the program status of neonatal hearing screening to compare and analyze the implementation of the UNHS program in 20 cities or provinces in China and 24 regions or countries around the world. The literature search in Chinese was conducted in the three most authoritative publication databases, CNKI (China National Knowledge Infrastructure), WANFANGDATA, and CQVIP (http://www.cqvip.com/ ). We searched all publications in those databases with the keywords "neonatal hearing screening" (in Chinese) between 2005 and 2014. English literature was searched using the same keywords (in English). The publication database included Medline and Web of Science, and the search time period was 2000–2014. Results: Shanghai was one of the first regions in China to implement UNHS, and its coverage rate was among the top regions by international comparison. The starting time of the UNHS program had no relationship with the Gross Domestic Product (GDP) per capita in the same year. Economic level serves as a threshold for carrying out UNHS but is not a linear contributor to the exact starting time of such a program. The screening coverage rate generally showed a rising trend with the increasing GDP per capita in China, but it had no relationship with the area's GDP per capita in selected regions and countries around the world. The system design of UNHS is the key factor influencing screening coverage. Policy makers, program administrators, and cost-sharing structures are important factors that influence the coverage rates of UNHS. Conclusion: When to carry out a UNHS program is determined by the willingness and preference of the local government, which is influenced by the area's social, political and cultural conditions. Mandatory hearing screening and minimal-cost to no-cost intervention are two pillars for a good coverage rate of UNHS. In terms of system design, decision-making, implementation, funding and the concrete implementation plan are all important factors affecting the implementation of the UNHS.